2011
DOI: 10.1124/jpet.111.182592
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin Prevents Liver Injury by Inhibition of High-Mobility Group Box 1 Production by Kupffer Cells after Ischemia-Reperfusion in Rats

Abstract: High-mobility group box 1 (HMGB1) acts as an early mediator of inflammation and organ damage in hepatic ischemia-reperfusion (I/R) injury. Glycyrrhizin is a natural anti-inflammatory and antiviral triterpene in clinical use. The purpose of this study was to investigate the effect of glycyrrhizin on liver injury caused by I/R and production of HMGB1 by Kupffer cells in rats. In the first test period, rats were given saline or glycyrrhizin 20 min before segmental hepatic warm I/R. Serum alanine aminotransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 32 publications
1
58
0
Order By: Relevance
“…Blocking HMGB1 activity by HMGB1-neutralizing antibody increases cyclin D1 expression and improves hepatocyte regeneration in APAP-injected mice (92). Inhibition of HMGB1 release by glycyrrhizin also improves hepatocyte regeneration after I/R in rats (48). These studies suggest that extracellular HMGB1 limits liver regeneration, although the potential mechanism of this association still remains largely unknown.…”
Section: Hmgb1 and Liver Regenerationmentioning
confidence: 82%
See 1 more Smart Citation
“…Blocking HMGB1 activity by HMGB1-neutralizing antibody increases cyclin D1 expression and improves hepatocyte regeneration in APAP-injected mice (92). Inhibition of HMGB1 release by glycyrrhizin also improves hepatocyte regeneration after I/R in rats (48). These studies suggest that extracellular HMGB1 limits liver regeneration, although the potential mechanism of this association still remains largely unknown.…”
Section: Hmgb1 and Liver Regenerationmentioning
confidence: 82%
“…Recent studies show that BÎČ15-42 (the fibrin-derived peptide), PNU-282987 (a selective α7 nicotinic acetylcholine receptor agonist), EPC-K1 (the vitamin E derivative), melatonin, cisplatin and glycyrrhizin attenuate warm liver I/R damage partly through inhibition of HMGB1 release (47)(48)(49)(50)(51)(52). Interestingly, pretreatment of mice with HMGB1 protein significantly decreased liver I/R injury through upregulation of IL-1R-associated kinase-M, a negative regulator of TLR4 signaling (53).…”
Section: Hmgb1 and Liver I/rmentioning
confidence: 99%
“…Glycyrrhizic acid (GA), the main logic activities such as antioxidative, anti-inflammatory, antiulcerous, antidotal, antiallergic, antiviral, immunomodulating, hepatoprotective, and cardioprotective properties (19)(20)(21)(22). It was demonstrated that GA played an important role in the inhibition of HMGB1 (23,24); therefore, we also aimed to evaluate the effect of GA as an inhibitor of hypoxia trophoblast (including PMT and JEG-3) HMGB1 induced hyperpermeability of endothelial cells (ECs), including HUVECs and mouse arterial endothelial cells [MAECs].…”
mentioning
confidence: 99%
“…Therefore, strategies disrupting TGF-b1/Smad signaling undoubtedly have therapeutic potential in the clinical treatment of PF. High-mobility group box 1 (HMGB1) is a transcription factor-like protein that acts as a danger signal in inflammatory diseases, tissue injury, as well as fibrotic diseases (Rowe et al, 2008;Ebina et al, 2011;Ogiku et al, 2011;Lee et al, 2013;Griffin et al, 2014;Li et al, 2014a). In lung tissues from patients with PF, HMGB1 is predominantly expressed in alveolar macrophages, infiltrating inflammatory cells, and epithelial cells (Hamada et al, 2008).…”
Section: Introductionmentioning
confidence: 99%